Combined effects of GSTM1 and GSTT1 polymorphisms on breast cancer risk: A MOOSE-compliant meta-analysis and false-positive report probabilities test. Issue 6 (February 2019) - Miao, Li-Feng; Wang, Xiao-Yan; Ye, Xiang-Hua; Cui, Meng-Shen; He, Xiao-Feng
Abstract : Abstract: Many molecular epidemiology studies have reported an association between the combined effects of glutathione S-transferase M1 ( GSTM1 ) and glutathione S-transferase T1 ( GSTT1 ) polymorphisms on breast cancer risk. However, the results have been controversial. A meta-analysis was performed to clarify this issue. Meta-analysis of observational studies in epidemiology guidelines was used. Pooled the crude odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random-effects model or fixed-effects model. Several subgroup analyses were conducted by ethnicity, source of control, matching, and menopausal status. In addition, we also performed sensitivity analysis and publication bias. Moreover, a false-positive report probability (FPRP) test was applied to assess positive results. A significantly increased breast cancer risk was observed in overall population ( GSTM1 null/ GSTT1 present [ − + ] vs GSTM1 present/ GSTT1 present [ + + ]: OR = 1.19, 95% CI: 1.03–1.36, GSTM1 null/ GSTT1 null [ − − ] vs + + : OR = 1.63, 95% CI: 1.29–2.06, ( − + ) + GSTM1 present/ GSTT1 null ( + − ) vs + + : OR = 1.17, 95% CI: 1.05–1.31, ( − + ) + ( + − ) + ( − − ) vs + + : OR = 1.27, 95% CI: 1.12–1.44, and − − vs ( − + ) + ( + − ) + ( + + ): OR = 1.39, 95% CI: 1.17–1.66) and several subgroup analyses, such as Caucasians, Indians, postmenopausal women, and so on. However, positive results were only considered noteworthy in overall population ( − − vs + + : FPRP = 0.150 and ( − + ) + ( + − ) + ( − − ) vs + + : FPRP = 0.162). Moreover, no significant association was observed when we used the trim and fill method to adjust the pooled data from all populations. Further, none of positive results of sensitivity analysis were considered noteworthy (FPRP >0.2). These positive findings should be interpreted with caution and indicate that an increased breast cancer risk may most likely result from false-positive results, rather than from true associations or biological factors on the combined effects of GSTM1 and GSTT1. Future studies should be based on sample sizes well-powered and attention needs to be paid to study design to further identify this issue.